Synthesis of 1,2,4,5-oxadiazaboroles by three-component condensations of hydroxylamines, nitriles, and diarylborinic acids - Ge, Zhenlu; Lough, Alan J.; Taylor, Mark S. (Canadian Journal of Chemistry, 2023)
A method for the synthesis of substituted 1,2,4,5-oxadiazaboroles is described, in which hydroxylamines, nitriles, and diarylborinic acids engage in a three-component condensation reaction. The protocol provides access to a substitution pattern that is not readily available through other methods?namely, 2,3-disubstitution, with a tetracoordinate boron center. Structures of representative members of this class of heterocycles were determined by single crystal X-ray diffraction analysis.A method for the synthesis of substituted 1,2,4,5-oxadiazaboroles is described, in which hydroxylamines, nitriles, and diarylborinic acids engage in a three-component condensation reaction. The protocol provides access to a substitution pattern that is not readily available through other methods?namely, 2,3-disubstitution, with a tetracoordinate boron center. Structures of representative members of this class of heterocycles were determined by single crystal X-ray diffraction analysis.